Semi-Formal Rules As a Factor in the Dynamics of the Efficiency of Formal Rules of Financial Monitoring - Volosnikova Nataliia M.; Maksymenko Iana A.; Serzhanov Vitaliy V.; Abramov Fedir V. (Bìznes Inform, 2023)
The article is aimed at defining the causes and consequences of the emergence and spread in the system of financial monitoring of semi-formal rules along with determining the measures to prevent them. It is shown that the efficiency of the financial monitoring system is determined by the efficiency of two groups of formal rules: formal rules of financial monitoring and formal rules of financial investigations. In addition to internal factors, the inefficiency of formal rules of financial monitoring may be caused by the spread of semi-formal rules. It is identified that the reason for the emergence and spread of semi-formal rules in the financial monitoring system is the broad discretionary powers granted to the official by both formal rules of financial monitoring and formal rules of financial investigations. The formation of semi-formal rules in the system of financial monitoring, like other cases of the formation of semi-formal rules, is accompanied by static and dynamic effects. The static effect of the formation of semi-formal rules is accompanied by a sharp drop in the effectiveness of the effective formal rules of financial monitoring. The main threat of the dynamic effect is the long-term decline in the efficiency of formal rules of financial monitoring. It is proved that of the two main conceptions of preventing the formation of semi-formal rules, i. e., limiting the discretionary powers of an official and restoring the efficiency of market mechanisms or imitating their correct operation, in the case of a financial monitoring system, only the last of these conceptions can be involved. A key element in the implementation of the restoration of the operability of market mechanisms or imitation of their correct operation is the delegation of basic monitoring functions to the actors who are able to perform the relevant functions with the lowest level of transaction costs of bureaucratic procedures.